Computer simulation of the performance of a thermosyphon solar water-heater - Lee, WenShiang; Wilson, Derek R.; Michaelides, Ioannis (My University, 1992)
The instantaneous collector-efficiency has been determined as a function of the time of day and correlated with the thermosyphonic-flow rate of water and the temperature difference between the water at the collector's inlet and outlet. The model was also used to predict the monthly and yearly solar-contribution of the system for two different load profiles. The results of the simulation indicate that the yearly solar contribution of the system for a low-consumption profile is about 89% as compared with 63% for a high consumption pattern.
Keywords: Water heaters; Energy conservation; Solar energy